A secured and reliable communication scheme in cognitive hybrid ARQ-aided smart city. (January 2020) - Khan, Fazlullah; Rehman, Ateeq ur; Jan, Mian Ahmad
Abstract: Due to advancements in communication technologies, specifically, the Internet of Things (IoT)-based smart cities, the allocation of spectral bands is a major challenge. To overcome this challenge, the cognitive radio network (CRN) has widely been accepted for efficient utilization of the available spectrum. Hence, efficient spectrum utilization and secured communication have attracted significant attention in recent years. However, due to the involvement of smart wireless devices in CRN, the cognitive radio (CR) systems are vulnerable to security threats that mainly target the weaknesses of CR communication and networking. Considering the efficient utilization of spectrum and secured smart city applications, this paper proposes a Secured and Reliable Cognitive Hybrid Automatic Repeat reQuest (SRC-HARQ) scheme. The SRC-HARQ models the primary user (PU) channel by Hidden Markov Model (HMM) to identify the unoccupied spaces. Based on the HMM results, the cluster head (CH) in a smart city determines the activity pattern of PUs and detects idle channels. After the detection of an idle channel, the CH broadcasts a beacon. Upon the reception of a beacon, each member node responds with a ready-to-send (RTS) message along with an encrypted message. The CH replies with a clear-to-send (CTS) signal after the successful decryption of the received message. Furthermore, a 4-state Markov Chain is used for reliability in terms of false alarm and misdetection. The closed-form expressions for mean packet delay, end-to-end delay, and throughput are derived and validated using Monte Carlo simulations.